Grey Wolf Algorithm in Coordinated Hydro and Wind Power Generation - Xing LI; Xiuyuan YANG; Lijie WANG (发电技术)
Wind is stochastic that trouble the grid power balance and make wind curtailment occur. The wind power and hydropower could cooperate operation to reduce the influence of wind power fluctuation. Through making full use of the regulating ability of hydropower and wind energy, the coordinated operation of wind power and hydropower can be realized by controlling hydropower units, so that the wind and hydropower coordinating operation system will output according to the plan, stabilize the power system. To achieve the coordinated operation of wind power and hydropower and improve the stationarity of the coordinate output, the Grey Wolf algorithm was used to optimize the PID control of hydraulic turbine, to facilitate hydropower steadily track the change of wind power and make the output of wind power and hydropower output according to plan. The simulation results verified the effectiveness of the method.